The paradox of switching social medias: A mixed-method study of students' academic performance and social fatigue - Dharmawan, Awang; Setiadi, Tatak; Karli, Ihsan (SIMULACRA: JURNAL SOSIOLOGI, 2024)
This study investigates the relationships among social media switching behavior, social fatigue, and academic performance among Generation Z university students. Despite the pervasive use of social media among this demographic, there is a lack of understanding of how social media switching affects academic outcomes and well-being. To address this research gap, a mixed-methods approach with a cross-sectional design was employed, analyzing data from a survey of 200 first-year Communication Science students in the State University of Surabaya (Unesa), Indonesia. The results reveal a statistically significant positive correlation between frequent social media account switching and higher academic performance, but no significant relationships between social media switching and social fatigue, or between social fatigue and academic performance. By understanding these collectivist dynamics between social media usage, academic performance, and social fatigue, this will provide valuable insights for educators and policymakers to develop strategies that promote a healthier balance between digital engagement and academic responsibilities.